Cost-effectiveness analysis of serplulimab combination therapy versus chemotherapy alone for patients with extensive-stage small cell lung cancer - Zheng, Zhiwei; Chen, Hongcai; Cai, Hongfu (Frontiers in Oncology, 2024)
Background Serplulimab has shown promising results in the treatment of extensive-stage small cell lung cancer (ES-SCLC). This study aimed to evaluate the cost-effectiveness of serplulimab combination therapy compared to chemotherapy alone in patients with ES-SCLC from the Chinese healthcare system perspective. Methods A partitioned survival model was developed to simulate the costs and outcomes of patients receiving serplulimab combination therapy or chemotherapy alone over a time horizon of 10 years. Data on overall survival, progression-free survival, and adverse events were obtained from the ASTRUM-005 randomized clinical trial. Costs were estimated from a healthcare system perspective and included drug acquisition, administration, monitoring, and management of adverse events. One-way and probabilistic sensitivity analyses were conducted to assess the impact of uncertainty on the results. Results The base-case analysis showed that the combination of serplulimab and chemotherapy has demonstrated a significant increase in QALYs of 0.626 compared to chemotherapy alone. This improved outcome is accompanied by an additional cost of 10893.995. The ICER for incorporating serplulimab into the treatment regimen is 17402.548 per QALY gained. One-way sensitivity analysis confirmed the robustness of the findings. Probabilistic sensitivity analysis demonstrated that serplulimab combination therapy had a 97.40% high probability of being cost-effective compared to chemotherapy alone at the WTP thresholds. Conclusion In contrast to chemotherapy as a standalone treatment, the addition of serplulimab to chemotherapy is believed to offer potential cost-effectiveness as a preferred initial therapeutic approach for patients with ES-SCLC in China.